Integration of xylan extraction prior to kraft and sodaAQ pulping from South African grown Eucalyptus grandis, giant bamboo and sugarcane bagasse to produce paper pulps, value added biopolymers and fermentable sugars - Vena, Phumla Faith (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.